2017
DOI: 10.1111/wrr.12601
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction may promote keloid growth

Abstract: Keloid is a cutaneous fibroproliferative disorder. It results from impaired wound healing that generates persistent inflammation and extensive deposition of collagen fibers in the wound/scar. Keloids tend to be worse in hypertensive patients. The present prospective cross-sectional study assessed whether endothelial dysfunction, which occurs in hypertension, associates with keloid formation and progression. This study included randomly selected patients with keloids who were assessed for surgical keloid treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
0
20
0
1
Order By: Relevance
“…There is an interaction between these factors that may be mediated by an alteration in the ratio of metalloproteinase-1 matrix to tissue inhibitor of metalloproteinase-1 (MMP-1/TIMP-1) that promotes the deposition of extracellular matrix. Endothelial dysfunction, which also occurs in high blood pressure, may also be involved in the pathogenesis of keloid disorders [13]. In addition, activation of the renin-angiotensin system is known to cause angiotensin II-induced arterial vasoconstriction resulting in elevated blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…There is an interaction between these factors that may be mediated by an alteration in the ratio of metalloproteinase-1 matrix to tissue inhibitor of metalloproteinase-1 (MMP-1/TIMP-1) that promotes the deposition of extracellular matrix. Endothelial dysfunction, which also occurs in high blood pressure, may also be involved in the pathogenesis of keloid disorders [13]. In addition, activation of the renin-angiotensin system is known to cause angiotensin II-induced arterial vasoconstriction resulting in elevated blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction is a hallmark of skin fibrotic conditions such as pathological cutaneous scars and cystic fibrosis. For example, our logistic regression analysis showed that patients with keloids were significantly more likely than the non-keloid controls to have poor reactive hyperemia index and augmentation index values: both indices are measures of endothelial function [11]. In fact, endothelial dysfunction plays such an important role in pathological scar development and progression that these cutaneous scars can be classified as primary and secondary pathological scars depending on whether the associated endothelial dysfunction is due to congenital abnormalities (e.g., mutations) or to externally-generated systemic (e.g., hypertension) or local (e.g., the tension on the scar) conditions [4].…”
Section: Endothelial Dysfunction In Skin Fibrosismentioning
confidence: 88%
“…Improvement of KLs in hypertensive patients has been observed following treatment with anti-hypertensive medications, such as ACE inhibitors (66) and calcium channel blockers (69). Endothelial dysfunction, which also occurs in hypertension, may also participate in the pathogenesis of KD (1,70), and is associated with lung (71), liver (72), cardiac (73), and kidney (74) fibrosis.…”
Section: Hypertension and Keloid Disordermentioning
confidence: 99%